Dental CT: Third Eye in Dental Implants - Jaju, P. P Prashant P; Jaju, S. P Sushma P; Suvarna, P. V Prashant V; Dedhia, P. Pratik (Jaypee Brothers Medical Publishers, 2013)
The book DENTAL CT: THIRD EYE IN DENTAL IMPLANTS describes the various dental programs that have been optimized for dental applications of computed tomography. In particular, this book focuses on the utility of dental CT for implantology, oral and maxillofacial surgery, endodontics and periodontics. Dental implants are the best treatment options for people with partial or complete loss of natural teeth. Dental CT gives information on the available bone, the proximity of teeth to the proposed implant site and structures to be avoided in implant placement. The technique offers great help to oral implantologists. The step-wise dental CT procedures are explained. The maxillofacial landmarks can be clearly demonstrated in a three-dimensional view on dental CT. The only drawback of dental CT is the use of high radiation dose compared to conventional plain radiography. This can be overcome with cone beam computed tomography (CBCT) and utilization of magnetic resonance imaging. CBCT helps in the planned position of dental implants. The last chapter is on certain case studies with images which focus on the use of dental CT.